(Diptera:Culicidae) Culex quinquefasciatus ????? ?????? ??? ?????????? ???????? ?? ???? ????? ????? ?????? ????? - هيا عبد شاكر (مجلة علوم ذي قار, 2019)
The Present Study has been prepared to evaluate the efficacy of the aqueous , alcoholic Extract and Secondary Compounds of Myristica fragrans , Anabasis setifera , Capparis spinosa , Chenopodium murale , Cordia myxa and Glycyrrhiza glabra on the 4th larval instar of Culex quinquefasciatus , the results showed Significant difference with high mortality percentage rate reached 42.49% for alcoholic extract compared with